Seroprevalence of Hepatitis E among Blood Donors in Calabar - Ushie, Godwin; Akaba, Kingsley; Nwogoh, Benedict (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Hepatitis E virus is one of the reemerging pathogens of global concern with an increased risk of transmission by transfusion of blood and blood products. However, this has not been studied in our environment. Aim: The aim is to study the seroprevalence of HEV transmission by potential blood donors in Calabar. Materials and Methods: This is a cross-sectional study conducted at the UCTH Calabar. A total of 187 potential donors were enrolled. Serum IgM and IgG HEV antibodies were done on 182 donors. IgM and IgG HEV antibodies were measured using an enzyme-linked immunosorbent assay. Data generated were analyzed using the statistical package for social sciences IBM SPSS version 23. Results: One hundred and eighty-two participants in the study with a male-to-female ratio of 2.1:1; a mean age and standard deviation of 28.1 ± 5–7 years; 63.7%, 31.9%, and 4.4% of the study population were first-time, regular, and lapsed donors, respectively. Also, 57.1%, 41.8%, and 1.1% of the subject were voluntary, replacement, and remunerated donors; respectively. Fifty percent of the subjects were HEV seropositive, out of which 8.79% were positive for IgM-only anti-HEV antibodies, 86.81% were positive for IgG-only anti-HEV antibodies, and 7.69% were positive for both anti-HEV IgM/IgG antibodies. Conclusion: There is a high seroprevalence of HEV (IgM and IgG) among potential blood donors in Calabar. IgM antibodies reflect acute infections which may be subclinical as in our study population while IgG reflects past infection. The relatively high seroprevalence of IgM antibodies obtained in the index study has serious implications for transfusion safety, especially for the immunocompromised persons in the region.